The Effect of Prone Position for Increasing OXygen Saturation of COVID-19 Patients - I Gusti Ngurah Putu Jaya Antara; Ni Wayan Erik Juniantari; I Made Adi Ariawan; I Kadek Artawan (Babali Publisher, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease caused by the SARS-CoV-2 virus that attacks the respiratory system, Oxygen saturation (SpO2) is one of the indicators of the severity of COVID-19 infection. Prone position is given as a nurse's self-intervention in COVID-19 patients which can evidently increase oxygenation in patients characterized by increased oxygen saturation. This study aims to determine the effect of prone position for increasing oxygen saturation of COVID-19 patients. This study used a pre-experimental design with a one-group pre-post test design without a control group. Researchers measure oxygen saturation before (pre-test) and after (post-test) to perform prone position in COVID-19 patients. The study population was all COVID-19 patients treated in the Isolation Room of a hospital in Bali. The sample in the study was 30 people who met the research criteria using purposive sampling techniques. The results of the study were obtained before prone position the average oxygen saturation was 94.90% while after being given the intervention prone position became 98.40%. Based on the Wilcoxon test analysis obtained p-value = 0.001. It concluded that there was a significant effect of prone position for increasing oxygen saturation of COVID-19 patients. Nurses are expected to provide education about prone position for COVID-19 patients, and the patients is recommended to practice prone position exercise to accelerate healing and reduce mortality